An Ultrasound Model to Predict the Short-Term Effects of Endovascular Stent Placement in the Treatment of Carotid Artery Stenosis - Chen, Sheng-Jiang; Liu, Rui-Rui; Shang, Yi-Ran; Xie, Yu-Juan; Guo, Xiao-Han; Huang, Meng-Jiao; Yang, Xiao-Feng; Fu, Qi-Zhi; Qi, Ji-Sheng; Shen, Dong-Yan; Li, Jia-Yan (Frontiers in Cardiovascular Medicine, 2021)
Purpose: The present study aimed to explore the predictive ability of an ultrasound linear regression equation in patients undergoing endovascular stent placement (ESP) to treat carotid artery stenosis-induced ischemic stroke. Methods: Pearson's correlation coefficient of actual improvement rate (IR) and 10 preoperative ultrasound indices in the carotid arteries of 64 patients who underwent ESP were retrospectively analyzed. A predictive ultrasound model for the fitted IR after ESP was established. Results: Of the 10 preoperative ultrasound indices, peak systolic velocity (PSV) at stenosis was strongly correlated with postoperative actual IR (r = 0.622; P < 0.01). The unstable plaque index (UPI; r = 0.447), peak eccentricity ratio (r = 0.431), and plaque stiffness index (β; r = 0.512) moderately correlated with actual IR (P < 0.01). Furthermore, the resistance index (r = 0.325) and the dilation coefficient (r = 0.311) weakly correlated with actual IR (P < 0.05). There was no significant correlation between actual IR and the number of unstable plaques, area narrowing , pulsatility index, and compliance coefficient. In combination, morphological, hemodynamic, and physiological ultrasound indices can predict 62.39% of neurological deficits after ESP: fitted IR = 0.9816 − 0.1293β + 0.0504UPI − 0.1137PSV. Conclusion: Certain carotid ultrasound indices correlate with ESP outcomes. The multi-index predictive model can be used to evaluate the effects of ESP before surgery.